Chitosan–Nanolignin Aerogel with Microneedles-Based Architecture Obtained from Spent Sulfite Liquor - Ștefan-Ovidiu Dima; Naomi Tritean; Luiza Capră; Bogdan Trică; Mihai Sârbu; Florin Oancea (Chemistry Proceedings)
Sulfite liquor is the by-product of wood chips treatment. An alternative method for recovering the carbonaceous components from sulfite liquor was investigated. A 3% CS suspension surprisingly incorporated almost all the carbon–sulfite phase in an aerogel system rising up at the surface of a beige liquid phase. The resulting solid and liquid phases were analytically characterized usingTEM-EDX, XRD, FTIR, ICP-OES, and UV-Vis methods, respectively. The TEM-EDX analysis revealed nanoparticles and microneedles with high C, O, Na, and S contents ionotropically adsorbed by CS, with this new hybrid material appearing as a biopolymer–carbon–metal nanocomposite aerogel with potential adsorbent, catalytic, and/or semiconductive properties.